Kestabilan komoditi tunggal dengan menggunakan kaedah langsung Lyapunov - Yaacob, Yusof (Department of Mathematics, Faculty of Science, 1995)
A model proposed by Belair & Mackey [1] concerning price dynamics of a single commodity market is reconsidered with different demand price kernel. From the model, a delay differential equation is obtained. The stability of the equilibrium price is analyzed using the Lyapunov's direct method and it is shown that the equilibrium price is locally and uniformally stable.